2010
DOI: 10.1007/s00253-010-2981-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria and archaea involved in anaerobic digestion of distillers grains with solubles

Abstract: Cereal distillers grains, a by-product from bioethanol industry, proved to be a suitable feedstock for biogas production in laboratory scale anaerobic digesters. Five continuously stirred tank reactors were run under constant conditions and monitored for biogas production and composition along with other process parameters. Iron additives for sulfide precipitation significantly improved the process stability and efficiency, whereas aerobic pretreatment of the grains had no effect. The microbial communities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(77 citation statements)
references
References 60 publications
1
75
1
Order By: Relevance
“…These results are consistent with the study by Ziganshin et al [16] who also found a greater number of Bacterial TRFs in samples from a mesophylic digester processing distillers dry grains with solubles. However, these authors found almost twice the number of TRFs in both domains than were detected in this study.…”
Section: Archaea and Bacteria Trf Richnesssupporting
confidence: 83%
“…These results are consistent with the study by Ziganshin et al [16] who also found a greater number of Bacterial TRFs in samples from a mesophylic digester processing distillers dry grains with solubles. However, these authors found almost twice the number of TRFs in both domains than were detected in this study.…”
Section: Archaea and Bacteria Trf Richnesssupporting
confidence: 83%
“…Archaeal communities, among others, have been investigated by using anoxic reactors that utilized liquid manure and different agricultural products as substrates (17,23,26). Many studies that analyzed both the archaeal and bacterial communities (10,16,18,19,39,42) or only bacterial communities (7) were accomplished, but the majority of the microbially diverse populations in anaerobic digesters has still not yet been sampled, as revealed by a recent meta-analysis (25). Additionally, the majority of the sequences found could not be assigned to an established genus (25).…”
mentioning
confidence: 99%
“…The vial was immediately sealed with a butyl rubber stopper and an aluminum crimp. The concentration of VFAs was determined from the headspace by use of a 5890 series II gas chromatograph (Hewlett Packard, Palo Alto, CA, USA) as described earlier (18). For TAN analysis, an aliquot (125 l) of the solution was diluted to 1:2,000 with distilled water and the TAN was determined by a standard Nessler method using a benchtop spectrometer (DR 3900; Hach-Lange, Loveland, CO, USA).…”
mentioning
confidence: 99%